Factors Influencing Sustainable Supplier Selection: Evidence from Palm Oil Refining and Oleochemical Manufacturing Industry - Vijayakumaran, Suresh Anand; Abdul Rahim, Suzari; Ahmi, Aidi; Abdul Rahman, Nor Aida; Mazlan, Ahmad Uzair (International Journal of Supply Chain Management, 2020)
This study focuses on the sustainable supplier selection in Malaysia palm oil refining and oleochemical manufacturing industry. A sustainable supply chain could lead to smoothness in the long run and thus ensure higher excellence and productivity. It is important to have suppliers that adapt to the sustainability nature of the organisation in order for the entire supply chain to be productive. The independent variables which have been used for this study are the unit price, CSR engagement, and environmental competencies. The leading theory used to support this study is the triple bottom line theory and backed by the resource dependency theory and stakeholder’s theory. This study was aided by surveying 151 respondents who are directly from palm oil refining and oleochemical manufacturing sector, which is the population for this study. After using the statistical tools to analyse the data retrieved from the questionnaires, it has been inferred that the unit price, quality, and environmental competencies have a significant effect on the dependent variable whereas CSR Engagement does not have a significant relationship. This study highlights the implication in the form of theoretical and social perspectives. It concludes with the limitation and the future recommendation of sustainable supplier selection in Malaysia palm oil refining and oleochemical manufacturing industry.